Effects of Technologies on the Behavior and Academic Performance of Grade Four Pupils - San Buenaventura, Bernadette (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the effects of technologies on the behavior and academic performance of Grade Four pupils in public elementary schools in District I-A, City Schools Division of Antipolo during the School Year 2025–2026. Specifically, it examined the perceived effects of technology on pupils’ behavior in terms of digital addiction, social and emotional changes, and enhanced connectivity; identified differences in these effects according to selected demographic variables; assessed the pupils’ academic performance; and determined the relationship between the perceived effects of technology and academic performance. The study employed a descriptive survey research design complemented by documentary analysis. The respondents consisted of 390 randomly selected Grade Four pupils from Bagong Nayon I Elementary School, Dela Paz Elementary School, and Santa Cruz Elementary School, with the sample size determined using Slovin’s formula. Data were gathered through a validated researcher-made questionnaire, while pupils’ average grades served as the basis for measuring academic performance. Descriptive and inferential statistical tools were used to analyze the data. Findings revealed that the respondents were predominantly male, mostly first- and second-born children from families with more than two children, with monthly family incomes of ₱20,000 and above. Most parents were college undergraduates or graduates and were employed or self-employed. Technologies had a very high effect on enhanced connectivity, a high effect on social and emotional changes, and a moderate effect on digital addiction. No significant differences were found in the perceived effects of technology when grouped according to sex, sibling position, and number of children in the family, while significant differences existed based on monthly family income, parents’ educational attainment, and parents’ occupation. The pupils’ academic performance was generally satisfactory, and a significant relationship was established between the perceived effects of technology on behavior and academic performance. The study concluded that family socioeconomic and educational factors significantly influence pupils’ technology-related behavior, which, in turn, affects academic performance. It recommended implementing school-based intervention programs, strengthening parent-teacher collaboration to promote responsible technology use, adopting the proposed action plan, and conducting further studies incorporating additional variables.